Protein arginine methyl transferases‐3 and ‐5 increase cell surface expression of cardiac sodium channel. Issue 19 (31st July 2013) - Beltran-Alvarez, Pedro; Espejo, Alexsandra; Schmauder, Ralf; Beltran, Carlos; Mrowka, Ralf; Linke, Thomas; Batlle, Montserrat; Pérez-Villa, Félix; Pérez, Guillermo J.; Scornik, Fabiana S.; Benndorf, Klaus; Pagans, Sara; et al.
Abstract : The α‐subunit of the cardiac voltage‐gated sodium channel (NaV 1.5) plays a central role in cardiomyocyte excitability. We have recently reported that NaV 1.5 is post‐translationally modified by arginine methylation. Here, we aimed to identify the enzymes that methylate NaV 1.5, and to describe the role of arginine methylation on NaV 1.5 function. Our results show that protein arginine methyl transferase (PRMT)‐3 and ‐5 methylate NaV 1.5 in vitro, interact with NaV 1.5 in human embryonic kidney (HEK) cells, and increase NaV 1.5 current density by enhancing NaV 1.5 cell surface expression. Our observations are the first evidence of regulation of a voltage‐gated ion channel, including calcium, potassium, sodium and TRP channels, by arginine methylation. Abstract : We identify the protein arginine methyl transferases (PRMT) that methylate NaV 1.5. We describe the effect of PRMT on NaV 1.5 function. PRMT3 and PRMT5 increase NaV 1.5 cell surface expression. This is the first report showing that PRMT regulate a voltage‐gated ion channel.